2005
DOI: 10.1001/archinte.165.7.808
|View full text |Cite
|
Sign up to set email alerts
|

A Prescribing Cascade Involving Cholinesterase Inhibitors and Anticholinergic Drugs

Abstract: Use of cholinesterase inhibitors is associated with an increased risk of receiving an anticholinergic drug to manage urinary incontinence. The use of an anticholinergic drug in this setting may represent a clinically important prescribing cascade. Clinicians should consider the possible contributing role of cholinesterase inhibitors in new-onset or worsening urinary incontinence and the potential risk of coprescribing cholinesterase inhibitors and anticholinergic drugs to patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
151
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(161 citation statements)
references
References 25 publications
(34 reference statements)
1
151
0
9
Order By: Relevance
“…47 Side effects Practitioners should always consider that the use of a cholinesterase inhibitor may contribute to a new or worsening clinical presentation. For example, such use has been associated with an increased risk of urinary incontinence, 48 and donepezil has been associated with an increased use of hypnotics (presumably for the treatment of insomnia). 49 The most common side effects of cholinesterase inhibitors are gastrointestinal (e.g., anorexia, nausea, vomiting, diarrhea).…”
Section: Effectivenessmentioning
confidence: 99%
“…47 Side effects Practitioners should always consider that the use of a cholinesterase inhibitor may contribute to a new or worsening clinical presentation. For example, such use has been associated with an increased risk of urinary incontinence, 48 and donepezil has been associated with an increased use of hypnotics (presumably for the treatment of insomnia). 49 The most common side effects of cholinesterase inhibitors are gastrointestinal (e.g., anorexia, nausea, vomiting, diarrhea).…”
Section: Effectivenessmentioning
confidence: 99%
“…There are few studies that have confirmed PC using pharmacoepidemiological techniques that can be used by pharmacists to justify interventions. [8][9][10][11][12][13] Approximately 90% of respondents in our study were willing to read and incorporate future studies on DIAEs and PC in future patient interventions. Therefore, this may be an area of educational need and potential for expanded observational and interventional research.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
“…7 Previous studies have identified DIAEs resulting in PC. [8][9][10][11][12][13] Yet there is no published information on any member of the healthcare team's knowledge of PC and how this knowledge can be used clinically. In particular, pharmacists' and student pharmacists' understanding of DIAEs and PC or their willingness to participate in interventions to mitigate DIAEs and PC is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Como el parkinson inducido por antipsicóticos o metoclopramida 2 , o la diarrea e incontinencia urinaria inducido por inhibidores de la colinesterasa (donecepilo, rivastigmina etc) 22 .…”
Section: Polifarmacia Y Toxicidad Medicamentosaunclassified